Dynamic Alignment of the Forward-Proton Detectors at the LHC - R. Staszewski; M. Trzebiński; J. Chwastowski (Advances in High Energy Physics)
The dynamic alignment method of the forward proton detectors proposed by the CDF collaboration is reviewed. The applicability of the method at the LHC is discussed.